2012
DOI: 10.1002/14651858.cd004739.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen for idiopathic sudden sensorineural hearing loss and tinnitus

Abstract: For people with acute ISSHL, the application of HBOT significantly improved hearing, but the clinical significance remains unclear. We could not assess the effect of HBOT on tinnitus by pooled analysis. In view of the modest number of patients, methodological shortcomings and poor reporting, this result should be interpreted cautiously. An appropriately powered trial is justified to define those patients (if any) who can be expected to derive most benefit from HBOT.There is no evidence of a beneficial effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 19 publications
2
102
4
5
Order By: Relevance
“…168,[170][171][172][242][243][244] Results of studies detailing effectiveness of HBOT depend on the choice of outcome measures. 166 fees in academic institutions are approximately $600 to $700 per session, including both technical and professional fees. Typical treatments have consisted of 5 to 10 sessions.…”
Section: Supporting Textmentioning
confidence: 99%
“…168,[170][171][172][242][243][244] Results of studies detailing effectiveness of HBOT depend on the choice of outcome measures. 166 fees in academic institutions are approximately $600 to $700 per session, including both technical and professional fees. Typical treatments have consisted of 5 to 10 sessions.…”
Section: Supporting Textmentioning
confidence: 99%
“…[11] A recent Cochrane review indicated a significantly greater chance of a 25% increase in the average PTA level in patients receiving HBO therapy. [12] Although prospective clinical trials of salvage HBO therapy with a control group are limited, result of these studies showed some benefits in hearing improvement. [10,13,14] The results of salvage HBO therapy in previous studies are demonstrated in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, entendemos que estos resultados no son concluyentes por cuanto esta terapia se indicó sólo a aquellos pacientes que no habían mejorado tras los primeros cuatro días de terapia médica, por lo que para llegar a conclusiones válidas deberíamos de modificar y ampliar nuestros estudios. En la revisión de la bibliografía hemos encontrado opiniones contrapuestas pues frente a algunos autores creen que presenta interés terapéutico, otros no encuentran beneficio alguno [31][32][33] .…”
Section: Discussionunclassified